1981
DOI: 10.3758/bf03206138
|View full text |Cite
|
Sign up to set email alerts
|

Letter and word code interactions elicited by normally displayed words

Abstract: The dependence of visual word recognition on letter processing was investigated by measuring the effect of a cue word on subsequent target word processing for various degrees of cue/ target similarity. Using a simultaneous matching task (Experiments 1 and 2), modest facilitation was found for identical cue/target items only, whereas items that differed by a single letter led to substantial interference. Targets that shared internal or external letters with cues yielded latencies comparable to those for neutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Interestingly, the word superiority effect was explained in a manner similar to the prefigural account of figure-ground organization. Lawry and LaBerge (1981) proposed that word-level information was processed in parallel with or before letter information. This "prelexical" account suggested that word-level information might be bootstrapped from letter-feature information (i.e., edges and line segments), not from letter information itself.…”
Section: Toward a Grain Account Of Visual Processingmentioning
confidence: 99%
“…Interestingly, the word superiority effect was explained in a manner similar to the prefigural account of figure-ground organization. Lawry and LaBerge (1981) proposed that word-level information was processed in parallel with or before letter information. This "prelexical" account suggested that word-level information might be bootstrapped from letter-feature information (i.e., edges and line segments), not from letter information itself.…”
Section: Toward a Grain Account Of Visual Processingmentioning
confidence: 99%
“…Due to the subjects' experiences in reading, scanning across the array in this manner may have induced them to attempt to encode the entire letter string holistically. A substantial amount of evidence has accumulated to suggest that letter strings that constitute words can be encoded holistically without the preliminary identification of each letter in the string (Jacewicz, 1979;Johnson & Marmurek, 1978;Lawry & Laberge, 1981;McClelland, 1979) Purcell, Stanovich, and Spector (1978) found a WSE using A_E as word strings and V_H as unrelated letter strings, with C, G, P, and R as possible targets in the middle position. However, Paap and Newsome (1980a) placed selected digits (3, 6, 8, or 9) between the same sets of flanking letters and found significantly lower performance with the V and H flankers, leading them to conclude that the original effect was due to differential lateral masking.…”
mentioning
confidence: 99%
“…Since reversing the order of letters has been found to induce letter-by-letter analysis (Lawry & LaBerge, 1981), a WSE with the NR strings suggests that serial analysis of the positions in a string allows a WSE to emerge. Its absence with the RN and RR strings suggests that normal letter orientation is necessary to allow serial tests at the positions to proceed in a manner conducive to a WSE.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Lawry and LaBerge (1981) measured response latency to perform a lexical decision task on lowercase letter strings embodying each of the four combinations of orientation and order used in Experiment 1. Before each string was presented, a priming stimulus appeared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation